2009
DOI: 10.1051/ebr/2010001
|View full text |Cite
|
Sign up to set email alerts
|

Existence of vigorous lineages of crop-wild hybrids in Lettuce under field conditions

Abstract: Plant to plant gene flow is a route of environmental exposure for GM plants specifically since crosses with wild relatives could lead to the formation of more vigorous hybrids, which could increase the rate of introgression and the environmental impact. Here, we test the first step in the process of potential transgene introgression: whether hybrid vigor can be inherited to the next generation, which could lead to fixation of altered, i.e., elevated, quantitative traits. The potential for a permanent elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…It was also possible to identify "hotspots" of QTLs, which would also better be avoided as they are clearly important to the plant's performance and mostly show advantageous as well as disadvantageous effects for the respective crop alleles. This study was carried out on plant vigour, based on the previous knowledge that lettuce crop-wild hybrids undergo selection at an early stage of growth [9]. To our knowledge, this is the first study on introgression that combines a QTL analysis approach with different stress treatments to address the process of introgression.…”
Section: Discussionmentioning
confidence: 99%
“…It was also possible to identify "hotspots" of QTLs, which would also better be avoided as they are clearly important to the plant's performance and mostly show advantageous as well as disadvantageous effects for the respective crop alleles. This study was carried out on plant vigour, based on the previous knowledge that lettuce crop-wild hybrids undergo selection at an early stage of growth [9]. To our knowledge, this is the first study on introgression that combines a QTL analysis approach with different stress treatments to address the process of introgression.…”
Section: Discussionmentioning
confidence: 99%
“…Our study together with its related work on hybrid fitness in natural field conditions (Hooftman et al. 2005, 2007, 2009) follows the fate of parental genomes through several generations after hybridization between wild and cultivated lettuce.…”
Section: Discussionmentioning
confidence: 99%
“…2005). We suggest that a sorting of genotypes by mortality, favoring distinct genomic segments from one of the parents, under field conditions could be responsible (Hooftman et al. 2009).…”
Section: Introductionmentioning
confidence: 95%
“…2009). In a series of field experiments, Hooftman et al. (2005, 2007, 2009) showed that at least four generations of lettuce crop–wild hybrids had higher germination and survival rates than the wild parent.…”
Section: Introductionmentioning
confidence: 99%